Influência de diferenciados exercícios físicos na regeneração do nervo ciático de ratos : estudo funcional e morfológico - Lima, Pábula Thais Mauricio Rodrigues de (2010)
Peripheral nerve fibers are a frequent lesion target because of its distribution around organism. These lesions create motor, sensitive and autonomic alterations. Several experimental studies demonstrate a relationship between physical exercise practice and functional regeneration after a peripheral nerve lesion. However, studies that relates the metabolic way predominantly used during exercise practice with gains on nerve functional recuperation and the evolution of inflammatory process in lesion macroenvironment are scarce. The present research investigates influence of predominantly aerobic and anaerobic exercises, initiated immediately after lesion, on functional and morphological recuperation of rat ischiatic nerve submitted to axonotmesis. The left ischiatic nerve crush was achieved in Wistar rats through a temporary surgical clip, by the period of three minutes. At first day after lesion, remained for four weeks, anaerobic group swam with crescent overload and aerobic swam in crescent periods, while sedentary group was exempt of any physical exercise practice. Functional recovery was evaluated through Sciatic Static Index obtained at first, seventh, fourteenth, twentieth-first and twentieth-eighth days postlesion, with morphological study conduced at twentieth-eighth days postaxonotmesis. Functional results demonstrated a significant statistical difference between exercise and sedentary groups at twentieth-eighth days after lesion, but there was no statistical difference in functional recovery between aerobic and anaerobic groups in any of evaluated periods, like there was no difference in morphological aspects observed at twentieth-eighth days post-lesion between aerobic, anaerobic and sedentary groups.